Novel magnetic fibrin hydrogel scaffolds containing thrombin and growth factors conjugated iron oxide nanoparticles for tissue engineering - Ziv-Polat O (Dove Medical Press, 2012)
Ofra Ziv-Polat1, Hadas Skaat1, Abraham Shahar2, Shlomo Margel11Department of Chemistry, Bar-Ilan Institute of Nanotechnology and Advanced Materials, Ramat-Gan 52900, Israel; 2NVR Research Ltd, Nes-Ziona 74031, IsraelAbstract: Novel tissue-engineered magnetic fibrin hydrogel scaffolds were prepared by the interaction of thrombin-conjugated iron oxide magnetic nanoparticles with fibrinogen. In addition, stabilization of basal fibroblast growth factor (bFGF) was achieved by the covalent and physical conjugation of the growth factor to the magnetic nanoparticles. Adult nasal olfactory mucosa (NOM) cells were seeded in the transparent fibrin scaffolds in the absence or presence of the free or conjugated bFGF-iron oxide nanoparticles. The conjugated bFGF enhanced significantly the growth and differentiation of the NOM cells in the fibrin scaffolds, compared to the same or even five times higher concentration of the free bFGF. In the presence of the bFGF-conjugated magnetic nanoparticles, the cultured NOM cells proliferated and formed a three-dimensional interconnected network composed mainly of tapered bipolar cells. The magnetic properties of these matrices are due to the integration of the thrombin- and bFGF-conjugated magnetic nanoparticles within the scaffolds. The magnetic properties of these scaffolds may be used in future work for various applications, such as magnetic resonance visualization of the scaffolds after implantation and reloading the scaffolds via magnetic forces with bioactive agents, eg, growth factors bound to the iron oxide magnetic nanoparticles.Keywords: thrombin, fibroblast growth factor, fibrin scaffold, iron oxide nanoparticles, tissue engineering, magnetism, bioactive nanoparticle